Can Poor People's Health Be Harmed by Short-Term Economic Policies: India's Demonetization (International Journal of Innovative Research in Engineering & Management, 2021)
During November 2016, the Government of India (GOI)  devalued the extensively used Rs. 500 as well as Rs. 1,000  denomination. To tackle illegal money, counterfeit money, as  well as terrorist activities, a short-term economic policy known  as notebandi was implemented. The implementation of  (Notebandi) was disorganized, perplexing, and difficult,  leaving many people without access to cash in their daily life.  The poor, who de.pend on cash to survive, have experienced  economic alienation and even destitution. In this paper, we  argue that currency devaluation has harmed the poor  disproportionately, as well as we establish the significant links  among devaluation and health problems. Finally, we encourage  public health experts to actively monitor and study the health  implications of India's recent demonetization, and also future  policy measures, to aid governments in creating and  implementing economic plans that do not hurt people's health,  especially the poor.
Keywords: Demonetization; Economic Policy; Health; India